Methods and theory of teaching physical education in primary school - Palwaniyazova Nawbahar Abdreymovna; Baltabaeva Guzal Maqsetovna (Genius Journals, 2022)
Currently, the development of new theories and practices of physical education, including the upbringing of children and adolescents, their socio-pedagogical support and protection is a process that is considered an integral part of individual-oriented integrated physical education.
Keywords: Physical education; field of study; learning process; teaching theory and practice